Reality check for high-performance football: a study of coaching competences based on the International Sport Coaching Framework - Galdino, M.; Lesch, L.; Wicker, P. (International Sport Coaching Journal, 2023)
Theoretically, professional coaches should improve team performance through a sustained, progressive, and structured training and competitive program. Nevertheless, the reality poses different expectations around football activities in Brazil, where coaching spells have lasted on average 65 days during the domestic league season. Adopting the conceptual foundation designed by the International Sport Coaching Framework (ISCF), this research aims to examine the competences perceived to be important for professional football coaches and compare them to the ISCF. This study asks the following research question: what coaching competences are expected and valued in Brazilian football, and how do they compare to the ISCF? Qualitative, semistructured interviews were conducted with 29 head coaches and 30 staff members. A directed content analysis yielded similarities around the ISCF`s functional competences, while also outlining one additional category: deliver short-term winning results. The findings reveal a set of subcategories that support the contextual idiosyncrasies of high-performance football in Brazil. Within their domestic territory, elite coaches must navigate across a puzzle of nonfootball demands to adapt to their social and political reality which apparently ranks short-term game results above the essence of sport coaching practice.